A New Tool for Measuring the Diameter of Hemp Fiber - Addisu Ferede Tesema; Christopher D. Delhom; Christopher Turner; Md Abu Sayeed; Noureddine Abidi (Journal of Natural Fibers)
Hemp is a versatile and durable natural material with a long history of human use. This plant provides essential materials such as fiber, seeds, and oil. Hemp fiber is among the oldest, strongest, and most durable natural fibers available. Fiber diameter stands out as a key characteristic among the various measurable properties of fibers for determining yarn and fabric quality. Despite advances in fiber analysis, current methods for measuring fiber diameter lack the efficiency required for high-throughput sample evaluation. The Optical Fiber Diameter Analyzer has been identified as a potential tool to measure the diameter of hemp fibers. This study involves three distinct experiments: investigating the stability of the OFDA diameter measurement, measuring hemp fiber diameters, and investigating the effects of different treatments on raw hemp fiber diameter. The instrument demonstrated reliability and precision in short- and long-term use, providing consistent hemp fiber diameter measurements with minimal variation. We observed that both the degumming and cottonization processes improved the hemp fiber quality. The development of such techniques is needed to ensure quality and optimize processes within the expanding industrial hemp fiber sector. The results are encouraging; however, further validation using larger samples of commercial hemp will be required.